Triadic coercion : Israel's targeting of states that host nonstate actors - Pearlman, Wendy; Atzili, Boaz (Columbia studies in terrorism and irregular warfare., 2018)
In the post-Cold War era, an increasing number of conflicts involve states and non-state actors. Yet states often have difficulty fighting such groups due to their small size, secretive structures, lack of visible assets, and extremist ideologies. Given these circumstances, some analysts conclude that states cannot deter non-state actors directly, and instead recommend that states aim to deter other states that aid, abet, or host these non-state actors--a strategy Atzili and Pearlman term "triadic coercion." In this book, Pearlman and Atzili explain the strategic function of triadic coercion, outlining how 'coercer' states employ this strategy; under what circumstances it is successful; and why states pursue triadic coercion even when it is the non-rational option (i.e., when the 'host' state is too politically or militarily weak to take effective action against the non-state actor). They trace triadic coercion through Israel's over 65 years of conflict with non-state actors like Hezbollah that attack Israel from neighboring Arab states. Employing qualitative empirical analysis of a range of primary and secondary sources--including interviews with political and military leaders, journalists, and analysts--Atzili and Pearlman map out the ideas, relationships, and mechanisms that led Israel to take the course of action it did; the consequences; and why Israel continues to utilize this strategy despite past failures. The final chapter broadens in scope to analyze how Turkey and India utilize (and do not utilize) triadic coercion in different ways, partly due to their country-specific security cultures, and why triadic coercion will continue to be a key, evolving force in the international security landscape.